Perioperative Glycemic Control: Main Factor in Reducing Postoperative Complications in Diabetic Patients - Ariel Leonardo Alarcón Vela; Ximena Patricia Santacruz Solís; Ronelsys Martínez (Revista Finlay, 2023)
The incidence and prevalence of diabetes mellitus has increased exponentially worldwide in recent decades. Diabetic patients are more likely to suffer serious complications in surgical procedures compared to the general population. The objective of this article is to describe the repercussion of the perioperative hyperglycemic state in the post-surgical stage in diabetic patients. In order to achieve the stated objective, various works were consulted, which include the results of research with different modalities related to the subject. It was possible to appreciate that perioperative hyperglycemia is associated with adverse results in general surgery patients with diabetes mellitus, however, in patients who have achieved glycemic control with insulin therapy before the intervention, they did not present a greater risk than that which appears in subjects with good metabolic control. Glucose regulation in the perioperative stage is an important parameter in diabetic patients, which considerably reduces complications in surgical procedures, long stays in Intensive Care Units, and even death.